Flame retardant systems based on alkoxysilanes for wood protection - Giúdice, Carlos Alberto (2017)
The aim of this study was to formulate, develop, and determine the performance of flame-retardant systems for wood protection. Flame-retardant systems involve wood impregnation and intumescent coating application. The impregnation was made in two retention levels using silanes of low and high hydrophobicity (methyltriethoxysilane and n-octyltriethoxysilane, respectively); these silanes were conducted to polymerize by sol-gel process in wood pores. The intumescent coatings were formulated with a polymeric binder (hydroxy-functional acrylic resin) modified with n-octadecyltriethox- ysilane in two w/w ratios to combine the individual characteristics of each film-forming material. In this research, Pinus radiata panels were selected to study the performance of quoted flame-retardant systems. The results indicated excellent flame-retardant performance of some studied systems in two foot tunnel, in oxygen index cabin, and in horizontal-vertical chamber.